Developing and Validating a Religious Literacy Scale for Prospective Teachers: An EFA–CFA Study in The Society 5.0 Era - Rachmaningtyas, Nur Anisyah; Cahyo Adi Kistoro, Hanif; Jodi, Khairul Hamimah Mohamad (Lembaga Sosial Rumah Indonesia, 2025)
Purpose – This study aims to develop a valid and reliable instrument to measure the religious literacy of prospective teachers in the Society 5.0 era. Religious literacy is a crucial aspect that prospective teachers must possess to face the challenges of 21st-century education and serve as role models for students.Method – This study employed a development model with FGDs involving 7 experts to validate the instrument. The 25-item instrument covers five dimensions: religious knowledge, digital literacy use, digital learning skills, attitudes and values, and digital ethics. It was tested on 172 Islamic Education teacher candidates from various LPTKs, with data analyzed using EFA and CFA. Despite using a Likert scale, ML estimation was applied, as commonly done when scales have five or more categories. Findings – The analysis results showed that the instrument had good construct validity and high reliability (? = 0.915). The instrument developed in this study initially consisted of 34 items, which were then reduced to 25 items based on the results of a review by 9 experts using the Aiken Formula. Research Implications – This instrument acts as a competency map to guide educational institutions in developing more focused and contextual digital religious literacy programs. Thus, integrating digital religious literacy into the curriculum and academic culture is essential to prepare Islamic Education teachers who are both professional and exemplary in promoting moderate, wise, and relevant religious values in the digital era.